Entrepreneurial Competencies and Livelihood Improvement: The Moderating Role of Gender - Nassiuma, Bernard Kibeti (Advances in Social Sciences Research Journal, 2017)
This study examined the interactive effect of gender in the relationship between entrepreneurial competencies and livelihood improvement in Uasin Gishu and Bungoma counties in the Western part of Kenya. A survey approach was used to collect data. A matched sample of 101 male and female was generated for the study from a wider study undertaken in the study area. The criterion for participation in the study was experience of under three years of experience in operating the venture. A questionnaire was the main data collection tool. The findings reveal that the moderation results did not supported the hypotheses for the study. Practical implications are that the paper identifies gender as a critical influence and suggests that the relationship between gender and development of entrepreneurial competencies should be addressed through supportive policies that encourage and develop entrepreneurial competencies for enhanced livelihood improvement. The theoretical and methodological framework used in this study provides an enhanced understanding and developing literature on the interactive effect of gender in the relationship between entrepreneurial competencies and livelihood improvement research which constitutes originality.